Association between Inflammatory Biomarkers and Nutritional Status in Fatty Liver - Lim, Hee-Sook; Choi, Joungyun; Lee, Bora; Kim, Sang Gyune; Kim, Young Seok; Yoo, Jeong-Ju (Clinical nutrition research, 2020)
The prevalence and progression of non-alcoholic fatty liver disease (NAFLD) is mediated via several factors correlating with hepatic necroinflammation (adipokines/cytokines). This study was performed to analyze the level of inflammatory markers according to the presence of NAFLD and to identify related nutritional factors. A total of 80 adults were classified into 2 groups (healthy and NAFLD), and their body composition, blood tests, and eating habits were evaluated. In addition, inflammatory markers (adiponectin, high-sensitivity C-reactive protein [CRP], and tumor necrosis factor-alpha [TNF-α]), nutrient intake status, and dietary quality were compared. The quality of diet was assessed according to the nutrient adequacy ratio and the mean adequacy ratio (MAR). The NAFLD group had a higher body mass index (p < 0.001) than the healthy group and also carried significantly higher CRP levels (p < 0.001) but lower adiponectin (p = 0.001). TNF-α levels increased significantly with fatty liver grade (p = 0.023). The NAFLD group showed significantly higher intake of energy, carbohydrates, iron, sodium, vitamin A and saturated fatty acids, but significantly lower intake of zinc and vitamin E than the healthy group. The MAR values were slightly higher in the NAFLD group but without any significant difference. The levels of adiponectin and vitamin E showed a significant inverse correlation (p < 0.05). Nutritional management of NAFLD patients is important, and the intake of antioxidant and anti-inflammatory nutrients such as zinc and vitamin E should be emphasized.The prevalence and progression of non-alcoholic fatty liver disease (NAFLD) is mediated via several factors correlating with hepatic necroinflammation (adipokines/cytokines). This study was performed to analyze the level of inflammatory markers according to the presence of NAFLD and to identify related nutritional factors. A total of 80 adults were classified into 2 groups (healthy and NAFLD), and their body composition, blood tests, and eating habits were evaluated. In addition, inflammatory markers (adiponectin, high-sensitivity C-reactive protein [CRP], and tumor necrosis factor-alpha [TNF-α]), nutrient intake status, and dietary quality were compared. The quality of diet was assessed according to the nutrient adequacy ratio and the mean adequacy ratio (MAR). The NAFLD group had a higher body mass index (p < 0.001) than the healthy group and also carried significantly higher CRP levels (p < 0.001) but lower adiponectin (p = 0.001). TNF-α levels increased significantly with fatty liver grade (p = 0.023). The NAFLD group showed significantly higher intake of energy, carbohydrates, iron, sodium, vitamin A and saturated fatty acids, but significantly lower intake of zinc and vitamin E than the healthy group. The MAR values were slightly higher in the NAFLD group but without any significant difference. The levels of adiponectin and vitamin E showed a significant inverse correlation (p < 0.05). Nutritional management of NAFLD patients is important, and the intake of antioxidant and anti-inflammatory nutrients such as zinc and vitamin E should be emphasized.